Embryonics Based Phased Array Antenna Structure With Self-Repair Ability - Sai Zhu (IEEE Access, 2020)
The reliability of phased array antenna can be improved with the self-repairing technology, and the existing self-repair method based on the TR module reconfiguration has problems such as slow calculation speed and difficulty in calculating the elements' mutual coupling, which is difficult to meet the application requirements. In this paper, a novel phased array antenna structure with self-repair ability is proposed. Based on the embryological electronics (embryonics), a novel phased array antenna structure with TR cell as the basic unit is constructed. The faulty TR cell can be detected and removed, and its influence on the phased array antenna's performance can be eliminated. The function and connection of faulty TR cell can be implemented by the normal TR cells and idle TR cells, the performance of phased array antenna can be repaired in real-time. TR cell, TR cell array and input/output switching control module are designed. The simulation tests show that, the phased array antenna with various fault conditions can be repaired in real-time based on the proposed structure, and the performance of phased array antenna can be repaired to the initial normal state with enough idle TR cells in array. Even without the idle TR cell, the performance of phased array antenna with fault can be improved through the self-repair. A new way for the design of phased array antenna design with self-repair ability is provided.